2020
DOI: 10.1002/jsfa.10394
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of essential oil extracted from pompia leaves against Penicillium digitatum

Abstract: BACKGROUND In recent years, interest in the use of natural compounds as possible substitutes for chemicals, to prevent microbial food spoilage has grown. The antimicrobial activity of the essential oils (EOs) is well known and nowadays there is renewed interest in their application as natural preservatives in postharvest management. The aims of this study were to characterize the EO extracted from pompia leaves and to evaluate its effectiveness for the control of the postharvest decay agent Penicillium digitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 37 publications
0
6
0
1
Order By: Relevance
“…A 6mm filter paper was placed in the center of each plate, and the same amount of essential oil and monomer was dripped on the filter paper. Fungi were fumigated using method by Danzi et al (2020). with a slight modification.…”
Section: The In Vitro Antibacterial Activity Of Essential Oils and A Monomer 1 8-cineole Discdiffusion Methodsmentioning
confidence: 99%
“…A 6mm filter paper was placed in the center of each plate, and the same amount of essential oil and monomer was dripped on the filter paper. Fungi were fumigated using method by Danzi et al (2020). with a slight modification.…”
Section: The In Vitro Antibacterial Activity Of Essential Oils and A Monomer 1 8-cineole Discdiffusion Methodsmentioning
confidence: 99%
“…Además, actúan como agentes antimicrobianos (Danzi et al, 2020) e insecticidas (Benelli & Pavela, 2018). Sobre esta base, los Eo se pueden aplicar en la conservación de alimentos (Fellenberg et al, 2020), en la medicina alternativa y en el área terapéutica (Rivera et al, 2015).…”
Section: Introductionunclassified
“…Also, they act as antimicrobial (Danzi et al, 2020), and insecticidal agents (Benelli & Pavela, 2018). On this basis, Eo can be applied in food preservation (Fellenberg et al, 2020), in alternative medicine, and in the therapeutic area (Rivera et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Fruit, and Sapindus saponaria L. fruit) has been reported to reduce postharvest fungal diseases in citrus fruits and other horticultural commodities ( 7 – 10 ). For instance, the essential oil extracted from pompia leaves effectively controlled the growth of P. digitatum ( 8 ). Moreover, the results showed that the activity of the ethanol extract of Sapindus saponaria L. fruit against Colletotrichum Musae was similar to that of thiabendazole at a 500-μg/ml concentration ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…The application of several plant extracts (e.g., pomegranate peel, pompia leave, Ficus hirta Vahl. Fruit, and Sapindus saponaria L. fruit) has been reported to reduce postharvest fungal diseases in citrus fruits and other horticultural commodities (7)(8)(9)(10). For instance, the essential oil extracted from pompia leaves effectively controlled the growth of P. digitatum (8).…”
Section: Introductionmentioning
confidence: 99%